ANALYSIS OF CONSOLIDATED ANNUAL FINANCIAL REPORT PT BANK CENTRAL ASIA TBK (BBCA) PERIOD 2023-2024 - Najmul Basim; Ariska Ananda P; Safrizal; Masdi; Saharuddin (PT. Radja Intercontinental Publishing, 2024)
Abstract*